New varieties of Pine Strawberry fragaria grandiflora ehrh - Н. В. Павлюк (Plant Varieties Studying and Protection)
It is presented brief description of Wild Strawberry varieties included to State Register of Plant Varieties, which are applied for extension in Ukraine in 2006, as well as morphological and biological features of the plant and its value.